Bayesian learning in financial markets: Testing for the relevance of information precision in price discovery - Nikolaus Hautsch; Dieter Hess (University of Cologne, Centre for Financial Research (CFR), 2004)
An important claim of Bayesian learning and a standard assumption in price discovery models is that the strength of the price impact of unanticipated information depends on the precision of the news. In this paper, we test for this assumption by analyzing intra-day price responses of CBOT T-bond futures to U.S. employment announcements. By employing additional detail information besides the widely used headline figures, we extract release-specific precision measures which allow to test for the claim of Bayesian updating. We find that the price impact of more precise information is significantly stronger. The results remain stable even after controlling for an asymmetric price response to 'good' and 'bad' news. – – Preise auf Kapitalmärkten werden durch nicht-antizipierte Informationen getrieben. Eine zentrale Aussage Baysianischer Lernmodelle impliziert, dass die Stärke der Preisreaktion einerseits von der Höhe der nicht antizipierten Komponente abhängt, andererseits aber auch von der Präzision der Informationen bestimmt wird. Auf Basis von Hochfrequenzdaten untersuchen wir den Einfluss von Veröffentlichungen des US-Arbeitsmarktberichts auf den Preis des CBOT T-Bond Futures. Neben den Kernkennzahlen des US-Arbeitsmarktberichts berücksichtigen wir ergänzende Detailinformationen. Mit Hilfe dieser Zusatzinformationen konstruieren wir ein Maß für die Präzision der Kernkennzahlen, welches uns erlaubt, die Aussage Baysianischer Lernmodelle zu testen. Wir finden, dass die Preise des T-Bond Futures stärker auf präzisere Informationen reagieren. Dieses Ergebnis gilt insbesondere auch dann, wenn wir für asymmetrische Preisreaktionen bezüglich positiver bzw. negativer Informationen kontrollieren.
Keywords: E44; G14; 330; Bayesian learning; information precision; macroeconomic announcements; asymmetric price response; financial markets; high-frequency data